2021
DOI: 10.3389/fnmol.2021.730604
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Protein PGAM5 Emerges as a New Regulator in Neurological Diseases

Abstract: As mitochondrial dysfunction has increasingly been implicated in neurological diseases, much of the investigation focuses on the response of the mitochondria. It appears that mitochondria can respond to external stimuli speedy fast, in seconds. Understanding how mitochondria sense the signal and communicate with cytosolic pathways are keys to understand mitochondrial regulation in diseases or in response to trauma. It was not until recently that a novel mitochondrial protein, phosphoglycerate mutase family mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Deletion of PGAM5 has been shown to result in Parkinson's-like movement disorder in mice (Lu et al, 2014) and T cell dysfunction in primary cells (Panda et al, 2016). While its diverse roles largely remain to be uncovered (Liang et al, 2021), a novel PGAM5 inhibitor was recently suggested as a potential therapeutic for brain ischemic stroke (Gao et al, 2021). We observed that PGAM5 displays elevated levels in the mitochondria isolated from brain, SKM and spleen, possibly explaining the tissue-specific phenotypes induced by its absence and where in the body molecules targeting its phosphatase activity would exert their effects.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of PGAM5 has been shown to result in Parkinson's-like movement disorder in mice (Lu et al, 2014) and T cell dysfunction in primary cells (Panda et al, 2016). While its diverse roles largely remain to be uncovered (Liang et al, 2021), a novel PGAM5 inhibitor was recently suggested as a potential therapeutic for brain ischemic stroke (Gao et al, 2021). We observed that PGAM5 displays elevated levels in the mitochondria isolated from brain, SKM and spleen, possibly explaining the tissue-specific phenotypes induced by its absence and where in the body molecules targeting its phosphatase activity would exert their effects.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoglycerate mutase 5 (PGAM5) is a mitochondrial serine [Ser)/threonine [Thr) phosphatase usually located in the inner mitochondrial membrane and regulates mitochondrial dynamics and programmed cell death [ 54 ]. PGAM5 also regulates mitophagy through different signaling pathways, contributing to cellular senescence, neurological diseases, and cancer [ 55 , 56 , 57 ]. SQSTM1, particularly (SQSTM1)/p62, is a soluble autophagy receptor with LIR motifs and one ubiquitin-binding domain at the C-terminus, which initiates selective autophagy in cells [ 37 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…PGAM family proteins possess a conserved PGAM domain that catalyzes mutase and/or phosphatase activities (Sadatomi et al, 2013;Cheng et al, 2021;Liang et al, 2021). PGAM5 lacks mutase activity, but mediates phosphatase activity and plays a regulatory role in mitochondrial dynamics and cell death (Sadatomi et al, 2013;Cheng et al, 2021;Liang et al, 2021). PGAM5 localizes to mitochondria via its N-terminal TM domain (Lo and Hannink, 2008).…”
Section: Regulation Of Bcl-rambo-induced Apoptosis and Mitophagy By P...mentioning
confidence: 99%